Planning and Implementation of Construction Investments - The Basic Stage of Works - Noga, Karol (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of this article is the evaluation of geodetic and geotechnical works with the use of an appropriate program for this type of work. On the example of a selected investment in Podkarpacie, the research analyzed the validity of conducting current geodetic and geotechnical control works. It should be emphasized that most of the technical specifications do not recommend the use of this type of control work. The paper presents exemplary test results and calculations based on the software used.
Keywords: spatial planning; construction investments; geodesy works; geotechnical works; valuation of works; software of solid volume; planowanie przestrzenne; inwestycje budowlane; prace geodezyjne; prace geotechniczne; wycena prac